Penerapan Standar Akuntansi Keuangan Entitsas Mikro, Kecil dan Menengah (SAK-EMKM) Pada Usaha Mikro Bakso Tenes Pasuruan Di Manado - Murniyati; Elim, Inggriani; Sardjono, Olivia (Universitas Sam Ratulangi, 2023)
Indonesia has a financial reporting standard called SAK-EMKM (Micro, Small and Medium Entity Financial Accounting Standards) specifically for MSMEs (Micro, Small and Medium Enterprises) which can be used as a reference in MSME financial reporting which is effective from 1 January 2018. This study aims to determine the application of SAK EMKM to the Bakso Tenes Pasuruan micro business in Manado. This type of research is a qualitative research with a descriptive method approach. The results of the research on the financial records of Bakso Tenes Pasuruan are still simple, owners and employees have not carried out recording activities and preparation of financial reports. In the financial statements of Bakso Tenes Pasuruan which were compiled by the author based on SAK-EMKM, there are 3 reports, namely a statement of financial position, a statement of profit and loss and a report of notes on financial statements which provide information about an explanation of the value of an item presented in the financial statements.